2018
DOI: 10.2196/jmir.9485
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Drivers and Barriers to the Adoption of eMental Health by Psychologists: The Construction of the Levels of Adoption of eMental Health Model

Abstract: BackgroundThe internet offers major opportunities in supporting mental health care, and a variety of technology-mediated mental and behavioral health services have been developed. Yet, despite growing evidence for the effectiveness of these services, their acceptance and use in clinical practice remains low. So far, the current literature still lacks a structured insight into the experienced drivers and barriers to the adoption of electronic mental health (eMental health) from the perspective of clinical psych… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
146
1
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(172 citation statements)
references
References 49 publications
11
146
1
14
Order By: Relevance
“…This may indicate that with experience, perceptions on these important clinical factors of bCBT will change and that when promoting uptake, therapists' needs can shift. This is consistent with Feijt et al [41] who showed that there are different barriers and facilitators depending on the level of therapist experience with online services, and that potentially, the experience level has unique requirements to be addressed when it comes to the uptake of Internet-based interventions.…”
Section: Level Of Experiencesupporting
confidence: 89%
“…This may indicate that with experience, perceptions on these important clinical factors of bCBT will change and that when promoting uptake, therapists' needs can shift. This is consistent with Feijt et al [41] who showed that there are different barriers and facilitators depending on the level of therapist experience with online services, and that potentially, the experience level has unique requirements to be addressed when it comes to the uptake of Internet-based interventions.…”
Section: Level Of Experiencesupporting
confidence: 89%
“…TECHNOLOGY AND THERAPEUTIC CARE The application of technology in face-to-face mental health care continues to be contentious (Feijt, de Kort, Bongers, & IJsselsteljn, 2018;Perle, Langsam, & Nierenberg, 2011;Richards, Simpson, Bastiampillai, Pietrabissa, & Castelnuovo, 2016). Present-day face-to-face therapy, operating in a similar format to Sigmund Freud's foundational practice, is based at its core upon direct communication and interaction between the therapist and client in a private setting.…”
Section: Introductionmentioning
confidence: 99%
“…The use of technology to deliver mental health interventions proliferated in recent years, with eMental Health interventions providing accessibility to needed mental health interventions [1,2]for more people [3] and at greater frequency [4]. Use of eMental Health interventions are especially promising for vulnerable and marginalized populations like migrants.…”
Section: Introductionmentioning
confidence: 99%